Research on Partial Ordered Sets That Can Be Constructed as Effect Algebras - Hai-feng Zhang; Meng Zhou (Discrete Dynamics in Nature and Society)
In this paper, we study effect algebra-induced partial ordered sets. All possible cases of effect algebras generated by bounded partial ordered set MI of height 2 are given. In addition, the structure of chain effect algebra is studied carefully and the corresponding results are obtained.